Development of a functional stack of soil microbial fuel cells to power a water treatment reactor: From the lab to field trials in North East Brazil. (15th November 2020) - Dziegielowski, Jakub; Metcalfe, Benjamin; Villegas-Guzman, Paola; Martínez-Huitle, Carlos A.; Gorayeb, Adryane; Wenk, Jannis; Di Lorenzo, Mirella
Graphical abstract: Highlights: Development of a low-cost stack of soil microbial fuel cells for energy harvesting. Current generated in the field was within 12% of the current produced in the lab. The stack could charge a 600 mAh battery in 8.5 h to treat 1.4 L of water. The integrated system can treat up to 2.8 L of water per day in the field. Abstract: Worldwide over 700 million people lack access to energy and safe water. Population growth and climate change severely stress limited freshwater reserves, and the search for innovative and sustainabledecentralised water treatment technologies is more urgent than ever; especially in vulnerable areas like North East Brazil, where water access is heavily restricted. In this context, in this study the development and implementation, from the lab to the field, of a low-cost, sustainable and self-powered system for water treatment, is presented for the first time. The system consists of an array of soil microbial fuel cells (SMFCs) that powers an electrochemical reactor for water treatment. Each SMFC is characterised by a flat geometry, with the anode embedded into the soil and the cathode exposed to air. The soil acts as the electrode separator and as a source of both electroactive bacteria and organic matter. Each SMFC generates a power of 0.4 mW, which is increased up to 12.2 mW by electrically connecting 16 SMFCs in parallel, with stable performance over 140 days of operation. An upscaled system, consisting of a stack of 64 SMFCs, was subsequently installed at a primary school in Icapuí, North East of Brazil, demonstrating a treatment capacity of up to three litres of water per day when integrated with the electrochemical reactor. By demonstrating implementation from the lab to the field, our work provides an effective route for the scalability and practical application of SMFC stacks for energy generation and self-powered water purification in remote areas.